Debating Artificial Intelligence : The Fox versus the Hedgehog - Emmerson, Donald K. (2019)
Singapore in Southeast Asia and Stanford University in the United States are focal points for discussions of AI and how it can be made to help not hurt human beings. A recent panel at Stanford illustrates the difficulty and necessity of bringing both generalist and specialist perspectives to bear on the problem.